ANALISIS PENGARUH HARGA BATUBARA, HARGA MINYAK MENTAH, NILAI KURS, DAN INDEKS HANG SENG TERHADAP RETURN SAHAM SEKTOR PERTAMBANGAN BATUBARA - , Harry Nugroho Ardianto, Prof. Dr. Slamet Sugiri, MBA., Akt., CMA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Coal mining still becomes the prime commodity in Indonesia. It becomes the main attraction for investor to invest especially on coal mining sub sector companies. Not to many variations appropriate economic model to measure the effect of market risk on stock returns of coal so this economic model is expected to be used as a reference for investors. The results showed that the Hang Seng Index has the most strongest influence that can be a reference for investors and for companies in the coal mining sector to predict stock returns to be gained. Rupiah exchange rate on U.S. dollar also had a strong influence, where the use of the currency exchange rate dualism mining companies are commonly used. Prevail-hedging system delivers maximum contribution on financial condition in the company. Rupiah exchange rate weakened will gives benefit from difference of exchange rate that earned.